Effectiveness of Fish Sanctuaries in the Mabini Reserve, Philippines after a Decade of Protection - Solandt, Jean-Luc; Comley, James; Harding, Simon P.; Trono, Romeo; Raines, Peter (Silliman Journal, 2022)
Three marine no-take zones (fish sanctuaries) were 1 established by municipal ordinance in Mabini, Balayan Bay, Southern Luzon in the northern Philippines in 1991. Eleven years later Reef Check surveys were carried out by Coral Cay Conservation volunteers in order to assess reef fish populations and hard coral cover both inside and outside the no-take zones. Results indicated that within the Mabini reserve on the southwest Calumpan peninsula, hard coral cover compared favorably with the rest of the Philippines and Indo-Pacific region, especially in shallow (<10m) water where the coral cover in places was high (>50% in Cathedral and Arthur's Rock sanctuaries). Sanctuaries generally had higher hard coral cover than non-sanctuary areas, especially in shallow (5m) waters. In the Mabini reserve both predatory commercial fish families such as groupers (Serranidae) and herbivorous parrotfish (Scaridae) were low in abundance both inside and outside the sanctuaries at shallow and medium depths. The very small number of these reef fish indicates that the no-take areas are currently having little direct effect on increasing the abundance of commercially important reef fish species relative to surrounding unprotected reefs. Patterns of increased fish diversity could be seen inside sanctuaries, with individual parrotfish, bumphead parrotfish (Bolbonietopon muricatunt), and Scombridae all recorded on one or two dives in the sanctuaries at medium depths. It appears that hard coral cover had a positive influence on fish abundance in the whole Mabini reserve. Sanctuaries also had a positive impact on reef fish diversity at medium depths compared to areas outside the sanctuaries, but had limited influence on diversity at shallow depths. Fish feeding by dive operators within Cathedral sanctuary may increase the diversity and abundance of smaller site-attached species found at this popular dive site (e.g. butterflyfish). Results indicate that the fish sanctuaries may be too small and have too much surrounding fishing pressure and encroachment to have a significant positive effect on the biomass of more valuable commercial fish species in the area. However, our data imply that sanctuaries are showing some success in establishing greater fish family and species diversity.